Big data, big metadata and quantitative study of science: A workflow model for big scientometrics. Issue 1 (24th October 2017) - Bratt, Sarah; Hemsley, Jeff; Qin, Jian; Costa, Mark
ABSTRACT: Large cyberinfrastructure‐enabled data repositories generate massive amounts of metadata, enabling big data analytics to leverage on the intersection of technological and methodological advances in data science for the quantitative study of science. This paper introduces a definition of big metadata in the context of scientific data repositories and discusses the challenges in big metadata analytics due to the messiness, lack of structures suitable for analytics and heterogeneity in such big metadata. A methodological framework is proposed, which contains conceptual and computational workflows intercepting through collaborative documentation. The workflow‐based methodological framework promotes transparency and contributes to research reproducibility. The paper also describes the experience and lessons learned from a four‐year big metadata project involving all aspects of the workflow‐based methodologies. The methodological framework presented in this paper is a timely contribution to the field of scientometrics and the science of science and policy as the potential value of big metadata is drawing more attention from research and policy maker communities.